SMARCA4/BRG1-deficient NSCLC: a case report and literature review - He Zhang; Xiong-wen Tu; Yu-qing Wei; Zheng-zheng Ni; Liang Cheng; Wu, Juan (Journal of the Pakistan Medical Association, 2025)
Patients with non-small cell lung cancer (NSCLC) deficient in SMARCA4 (SMARCA4-dNSCLC) are commonly diagnosed at advanced stages with a poor prognosis. Although immune checkpoint inhibitors (ICIs) combined with platinum-based chemotherapy regimens are widely used, their efficacy in SMARCA4-dNSCLC patients remains suboptimal. Herein, we present the case of a SMARCA4-dNSCLC patient treated at Yijishan Hospital on January 18, 2023. Following our comprehensive treatment, our patient’s general condition and quality of life (QOL) have remained satisfactory, and there has been no disease progression to date. Keywords: NSCLC, SMARCA4-deficient, Treatment, Prognosis.